The look of a leader - Katherine Qianwen Sun; Michael L. Slepian; Modupe Akinola (PLoS ONE, 2025)
Women and minorities are underrepresented in top leadership roles. Besides “supply-side” explanations that focus on the applicant pool, we offer a novel “demand-side” explanation through perceptual imprinting. Using the reverse correlation method, we found that people’s visual templates of leaders are perceptually imprinted by White male leaders. Across 15 studies (N = 3929), we examine what people expect leaders to look like. As demonstrated by the reverse correlation method, compared to followers, people expected leaders to look more White and male. Across all social categories, people also expected leaders to look more dominant, competent, and powerful. But to look like a leader, Black and female leaders also needed to look likable. Additional differences were observed by participant gender. Thus, in addition to having biased perceptual representations of leaders, people also have different perceptual standards for different social groups, as expressed by different expectations for how leaders of different races and genders should look. (151 words).